The Impact of Employees’ Information Security Awareness on Information Security Behaviour - Melissa Indah Fianty (IJISTECH (International Journal of Information System and Technology), 2023)
Internal threats have been a hot topic in information security for several years. According to a 2018 Insider Threat Reports survey, 51% of users are more concerned about internal carelessness and negligence than 47% about external attacks. The availability of information has a vital role for companies today, including confidentiality and integrity in supporting company performance. Users or employees are an essential factor in many information security breaches. This study aims to determine whether security education & training, information security awareness, employee relations, employee accountability, organizational culture, and national culture significantly affect Information System Security Behavior. The sample of this research is employees who work at PT Infracom Technology. Sampling was carried out using the Likert Scale method, and data collection was carried out using questionnaires distributed directly to employees as many as 72 respondents. The statistical method uses Linear Regression Analysis, with statistical tests to test the hypothesis. The results showed a direct and significant influence between security training and education factors, information security awareness, employee relations, and employee responsibility. The most influential variable was employee accountability.